Crowdfunding for entrepreneurs : developing strategic advantage through entrepreneurial finance - Di Pietro, Francesca, 1987- (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"This is the first book of its kind to systematically integrate crowdfunding in the entrepreneurial finance research field and extends the current debate to show how crowdfunding can be leveraged as strategic tool to grow new ventures. Utilising original empirical evidence of companies that have raised funds via crowdfunding, it discusses the value-added services that the crowd provides to entrepreneurs, as well as how and under which conditions crowdfunding helps company development by facilitating subsequent access to critical financial and non-financial resources from external stakeholders. The first part introduces the most popular models and tactics for a successful crowdfunding campaign and illustrates the characteristics of the crowdfunding phenomenon and its evolution across the world during the last decade. The second part of the book, demonstrating how crowdfunding can be a starting point to seed financing, illustrates and discusses how entrepreneurs can use crowdfunding as a strategic tool for accessing subsequent resources from external stakeholders - showing the benefits, beyond capital, that entrepreneurs can gain from the crowd, as well as potential risks. Crowdfunding for Entrepreneurs is particularly useful for academics, advanced undergraduate and postgraduate students in entrepreneurship and innovation, entrepreneurial finance, strategic management, as well as professionals interested in how crowdfunding can be utilised as a strategic tool to create competitive advantage"--
5.2.2 Test the market and obtain public exposure -- 5.2.3 Attract investments from professional investors -- 5.2.4 Retain company control -- 5.2.5 Receive support from passionate investors -- 5.3 Strategic and financial benefits of equity crowdfunding -- 5.4 Risks related to equity crowdfunding -- 5.4.1 Entrepreneur risks -- 5.4.2 Investor risks -- 5.4.3 Platform risk -- Notes -- References -- 6: Equity crowdfunding as a strategic tool -- 6.1 Review of the literature on equity crowdfunding -- 6.2 Crowd investors as a source of knowledge and network
OCLC-licensed vendor bibliographic record.
Keywords: Crowd funding; Venture capital; BUSINESS & ECONOMICS / Finance; BUSINESS & ECONOMICS / Strategic Planning